Enhancement of surfactant efficacy during the cleanup of engine oil contaminated soil using salt and multi-walled carbon nanotubes - Bonal N.S.; Paramkusam B.R.; Basudhar P.K. (My University, 2025)
The study aims to enhance the efficacy of surfactants using salt and multi-walled carbon nanotubes (MWCNT) for washing used engine oil (UEO) contaminated soil and compare the geotechnical properties of contaminated soil before and after washing (batch washing and soil washing). From batch washing of the contaminated soil the efficacy of the cleaning process is established. Contamination of soil with hydrocarbons present in UEO significantly affects its’ engineering properties manifesting in no plasticity and low specific gravity; the corresponding optimum moisture content value is 6.42% while maximum dry density is 1.770 g/cc, which are considerably lower than those of the uncontaminated soil. The result also showed decrease in the values of cohesion intercept and increase in the friction angle values. The adopted soil washing technique resulted increase in specific gravity from 1.85 to 2.13 and cohesion from 0.443 to 1.04 kg/cm2 and substantial decrease in the friction angle from 31.16° to 17.14° when washed with most efficient combination of SDS surfactant along with sodium meta-silicate (salt) and MWCNT. Effectiveness of the washing of contaminated soil by batch processing and soil washing techniques has been established qualitatively. The efficiency of surfactant treatment has been observed to be increased significantly by the addition of salt and MWCNT. © 2018 Elsevier B.V.